The significant of urban form of Erbil City, Iraq - Akram, Omar Khasro; Ismail, Sumarni; Franco, Daniel Jose (IJETMAS, 2016)
Erbil is the capital of the Autonomous Region of the Kurdistan within the Federal Republic of Iraq and, according to the International Council on Monuments and Sites (ICOMOS), it’s considered the oldest continuously inhabited city in the world, with around 6000 of age, presenting, although its quick expansion, a relatively compact form when compared to other cities of similar size in Europe and North America. This paper addresses the issue of this unusual compact form, highlighting the history of Erbil city and how it grew around the Citadel present in its nucleus. A descriptive and interpretative approach is adopted to outline the irregular oval shape of the Erbil Citadel and its archaeological heritage, focusing also the need to preserve its facades and interior buildings and the master plans already designed which may change the actual city form and the way people live in it.